Weighted and Standardized Total Environmental Quality Index (TEQI) Approach in Assessing Environmental Components (Air, Soil and Water) - Ho, Pham Ngoc (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 3, 2011)
Abstract . The paper investigates an innovative approach in assessing integrated environmental quality using indices that have been applied in many countries, such as Belgium, the former Soviet Union countries, the United States and Canada. The approach (abbreviated as TEQI) is more innovative than other indexed approach. Concretely, in this approach, the important weight of studied parameter taking into account theirs poisonous levels and classification scale for assessment of environmental quality depending on total number of parameters n (2≤n≤100) were established by calculating from theoretical formulas, not be assigned as the others. The results of the application of TEQI to the assessment of soil (n=5), ground water (n=20) and air components (n=5) show that the ranking in TEQI corresponds to the actual monitored data. Keywords: index, weighted, standardized, scale, environmental components.